Against Epistemic Domination: A Review of the Decolonization of Qur'anic Studies and the Inclusivity of Knowledge - Achmad Syariful Afif; Abdullah Khoirur Rofiq; Adam Annural Haj (al-Afkar, Journal For Islamic Studies, 2025)
Decolonization of Al-Quran studies is a approach that aims to examine, challenge and overcome interpretations and methodologies that are influenced by the hegemony of knowledge, especially by "Western sciences". Decolonization offers an epistemic idea that is inclusive and egalitarian so that it does not give privilege to a particular way of knowing, a framework like this offers an interpretive discourse that is more open, intersectional, dynamic and equal. This qualitative research aims to elaborate on the idea of ​​decolonization in the study of the Qur'an and compare the ideas of thinkers to highlight the common ground of their thinking while maintaining and explaining existing differences, also emphasize the urgency of decolonization in Qur’anic Studies. So, the method used in this research is comparative analysis. This research concludes that decolonization provides several important meanings in the world of interpretation, such as 1). Equality between knowledges and ways of knowing, 2). Cross-cultural or intersectional studies and 3). Restoring ethical values ​​in knowledge and intensifying community involvement in the interpretation of the Koran. Apart from that, this discourse is still faced with various challenges, such as the potential for the emergence of a new style of essentialism that gives birth to neo-colonialism and resistance from some academic circles who still adhere to the traditional paradigm, feel threatened by changes in the structure of "intellectual power" and do not really care about the context and cultural reality of Islamic thought that continues to develop.